Does stress affect IVF outcomes? A prospective study of physiological and psychological stress in women undergoing IVF. Issue 1 (July 2019) - Miller, Netanella; Herzberger, Einat Haikin; Pasternak, Yael; Klement, Anat Hershko; Shavit, Tal; Yaniv, Rina Tamir; Ghetler, Yehudith; Neumark, Eran; Eisenberg, Michal Matzkin; Berkovitz, Arie; Shulman, Adrian; Wiser, Amir
Abstract: Research question: What are the effects of physiological and psychological stress on fertility outcomes for women undergoing IVF? Design: A prospective cohort study of 72 patients undergoing IVF in 2017 and 2018. Physiological stress was assessed by salivary cortisol measurements: (i) pretreatment, when the patient received the IVF protocol; (ii) before oocyte retrieval (follicular cortisol was also measured); and (iii) before embryo transfer. Emotional stress was evaluated at each assessment with the State-Trait Anxiety Inventory and a 1–10 Visual Analogue Scale (VAS, referred to as the 'Stress Scale'. Correlations between cortisol concentrations, psychological stress and IVF outcome were assessed. Results: Salivary cortisol concentrations increased by 28% from pretreatment phase (0.46 ± 0.28 μg/dl) to maximum concentration on oocyte retrieval day (0.59 ± 0.29 μg/dl, P = 0.029) and then decreased by 29% on embryo transfer day (0.42 ± 0.23 μg/dl, P = 0.0162). On embryo transfer day, cortisol among women in their first cycle was higher than women who underwent more than one treatment ( P = 0.024). Stress Scale score increased by 39% from pretreatment to a maximum score on oocyte retrieval day and then decreased by 12% on embryo transfer day. Salivary cortisol and Stress Scale were not related to subsequent embryo transfer, fertilization rate, embryo quality or clinical pregnancy rate. Follicular cortisol concentration was positively correlated with fertilization rate ( r = 0.4, P = 0.004). Conclusion: It can be cautiously concluded that physiological and psychological stress do not negatively affect IVF outcomes. Moreover, high follicular cortisol concentrations might have positive effects on pregnancy rates.